PEMANFAATAN RHIZOBACTERIA OROK-OROK (Crotalaria juncea L.) DAN JUMLAH BIJI DALAM POLONG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG TANAH (Arachis hypogaea L.) - Purnawati Listyasari; Maria Theresia Darini; Djoko Heru Pamungkas (JURNAL ILMIAH AGROUST, 2019)
The aim of this study was to determine the right concentration of rattlepod rhizobacteria and the number of seeds in pods on growth, yield and percentage of seeds in pods of peanut. The experiment was carried out in Sumber Gamol, Balecatur, Gamping, Sleman, Special Region of Yogyakarta. Location of research altitude Â± 94 m above sea level (masl), regosol soil type with soil pH 5,6 - 6,0 and temperatures between 24 - 32 oC, rain fall 2000 â€“ 3000 cc year-1. The experiment was arranged by Design Split Plots. The main plots were the concentration of rattlepod rhizobacteria (K), namely 1%, 2% and 3%, the subplots were the number of seeds in pods (P), namely seed pods 1, 2 and 3, each treatment 3 replication. Observation variables included plant height, number of branches, number of leaves, leaf area, leaf fresh weight, number of flowers, number of pods, percentage of pods, percentage of seeds in pods, plant fresh weight, plant dry weight, Relative Growth Rate (RGR) and seed weight per hectare. Data were analysis by analysis of variance followed by Duncan's Multiple Range Test at 5% significance level. Analysis result showed there was no interaction between the combination of rattlepod rhizobacteria concentrations and the number of seeds in the pod on the entire observation variable. The concentration of rattlepod rhizobacteria does not increase the growth and yield of peanuts. The number of seed pods 1 and 2 increases growth but does not increase the yield of peanuts. Seed pods 2 produced the highest percentage of 2 seed pods, while seeded pods 3 produced a significant data result and a lower percentage of 2 seed pods, but 3 seeded pods increased